Efektivitas Buku Saku PHBS di Sekolah dalam Meningkatkan Perilaku Hidup Bersih dan Sehat - Muthmainah Farida Hanif; Mury Ririanty; Iken Nafikadhini (Jurnal Kesehatan, 2018)
AbstractSchool children become one of the most vulnerable groups to health problems due to environmental factors and poor lifestyles, so they need for a strong support from the environment in the formation of Clean and Healthy Behavior (PHBS) among school children. The methods and props used in health promotion need to be given careful attention, so that the material or ingredients can easily accepted, assimilated and absorbed by the target. The PHBS pocketbook in school is one of publication media of health promotion which had been through expert test and late published, but the PHBS pocketbook in school has not done effectiveness test to the target audiences. This study aimed to analyze the effectiveness of PHBS pocketbook in schools in improving knowledge, attitudes and intentions of PHBS in primary school children. This research was a real experimental study used Pretest Posttest design with control group conducted in SDN Krembangan Selatan 10, SDN Perak Barat 6 and SDN Kemayoran 1. The results of this study indicate that the value of knowledge, attitude and intention are better after the intervention had given to the experimental group A through the PHBS pocketbook in school and counseling, as well as experiment group B through the PHBS pocketbook in school, while the control group has the same value because no intervention was done. PHBS pocketbook media in those school proved able to increase knowledge, attitude and intention in clean and healthy life behavior in elementary school children.Keywords: pocketbook, Effectiveness, Behavior, PHBS, School